Using computer‐assisted instruction to increase the eye gaze of children with autism. (6th November 2017) - Miller, Neal; Wyatt, Jennifer; Casey, Laura Baylot; Smith, J. Brian
Abstract : Many children diagnosed with autism spectrum disorders have difficulty making appropriate eye contact and engaging in joint attention. The current study evaluated a computer‐assisted instruction package (pairing visual stimuli with vocal stimuli) as a novel treatment to improve the eye gaze accuracy in 3 elementary school children with autism. The researchers measured the latency from a recorded verbal stimulus to the students making eye contact with pictures of familiar individuals displayed on a computer screen, and the duration for which eye gaze on the stimulus was maintained. An automated infrared camera system for measuring eye gaze was utilized that eliminated the need for an instructor to make subjective judgments regarding participants' eye gaze. For all three participants, duration of eye contact increased, and latency to responding decreased following exposure to the computer‐assisted instruction. The implications of these findings for the treatment of individuals with autism are discussed, along with suggestions for future research on the topic.